Analysis of the Impact of Sustainable Land Management Practices on Vegetation Cover in Balaka District, Malawi - Kilembe, Chikumbutso; Mzuza, Maureen Kapute (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 8, 2023)
Sustainable Land Management (SLM) practices are important to reduce land degradation, considering that 25% of global land is degraded. A study was conducted in Malikula micro-catchment in Balaka District to analyse the impact of SLM practices on vegetation. Quantitative and qualitative data were collected and analysed using a mixed methods approach. A household survey was conducted to collect information on existing SLM practices in the area and the factors influencing households to implement them. Selected Landsat Remote Sensing Imagery (LRSI) data for 30 years from 1991 to 2021 were downloaded and analysed in QGIS 3.22.10 (Biatoiweza) software using Semi-Automatic Classification Plugin (SCP) to determine LULC changes related to vegetation and Normalised Difference Vegetation Index (NDVI) over the study period. Additional land productivity and rainfall data obtained from the Balaka Agricultural Office and the Department of Climate Change and Meteorological Services (DCCMS), respectively, were also analysed. The results indicate that ISFM is the most practised SLM intervention and that the need for soil fertility improvement drives households to adopt it. In addition, households with access to extension services and more land have a higher probability of adopting SLM practices. Further, more female-headed households adopt SLM practices than male-headed households despite the latter being more knowledgeable. LULC analysis (Overall Accuracy and Kappa Coefficient of 89.2% and 0.78, respectively) show an increasing trend in dense and very dense vegetation cover at the expense of wetlands. Despite a decline in annual rainfall amounts during the study period, the study has found a positive correlation between mean NDVI and land area under RWH (R = 0.51), highlighting the impact of RWH on improved vegetation cover. The study recommends further gender analysis to understand SLM information asymmetry, more investment in extension services, promotion of SLM packages that appeal to farmers with limited land and exploration of innovative financing options for SLM practices to incentivise adoption. Lastly, the study recommends additional studies in the area to understand the decline in land area for wetlands.